Paraspinal Extraosseous Ewing's Sarcoma With Disseminated Metastases Masquerading As Pott's Spine (Bangladesh Journal of Medical Science, 2013)
A 16 years old girl presented with low back pain, fever and weakness in both lower limbs for 3 months. Plain radiograph shows lytic lesion in first sacral vertebra and multiple lung nodules. In suspicion of tuberculosis, antitubercular drugs were advised. But magnetic resonance imaging revealed right paraspinal soft tissue mass with multiple lesions in several vertebrae causing spinal canal compression alongwith lesions in iliac bones, sacrum, lung parenchyma and scalp tissue. Fine needle aspiration cytology and biopsy revealed Ewings sarcoma. Patient was referred to higher centre for chemotherapy/radiotherapy. Herein we report this rare case of extraosseous Ewings sarcoma with disseminated metastases masquerading as Potts spine. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 334-338 DOI: http://dx.doi.org/10.3329/bjms.v12i3.15447